Profil Status Identitas Religius pada Remaja Akhir - Prawitasari, Galuh (Universitas Ahmad Dahlan, 2017)
This study aimed to find out the profile of religious identity on late adolescents. This was a quantitative study with descriptive survey design. The subject of this study was 134 students of Guidance and Counseling Department of Yogyakarta State University who were taken by simple random sampling technique. The data were collected through Religious Identity scale. The data were analyzed by using descriptive statistics.Â The result of this study showed that 100 subjects were in the achievement status (75%), 27 subjects were in the searching moratorium status (20%), and seven subjects were in the foreclosure status (5%).Â The result of this study took a role as the basis for formulating a guidance and counseling service to develop the religious identity on late adolescents.